Seismic Assessment of Tall Buildings Designed According to the Turkish Building Earthquake Code - Ergunes, Orhan Ilkay; Aksu Ozkul, Tulay (Salehan Institute of Higher Education, 2022)
For the first time, the 2018 edition of the Turkish Building Earthquake Code has added a dedicated chapter for the design of high-rise buildings in earthquake-prone areas. Keeping in view the widely practised design option of rigid shear walls at the centre of a high-rise structure, the latest code has additionally defined limits for shear-wall axial forces in high-rise buildings. The new shear-wall axial force limits have not been independently investigated for optimal design and criticality. This calls for a detailed investigation of the newly defined axial force limits for the design of high-rise buildings in Turkey, where seismic activity has historically remained high. This study, therefore, investigates the effect of variation in limit values of shear wall axial forces on the collapse prevention of such buildings. A high-rise building designed entirely according to the code was chosen as the base model. The location of the building is in Istanbul, which has the highest number of tall buildings as compared to other cities in Turkey. A total of 7 alternative models were created by changing the concrete material class and the thickness of shear walls. This approach allowed us to quantify the effect of shear-wall thickness and its criticality against another important design consideration, i.e., the compressive strength of concrete. Forty different earthquake ground motion records were used to analyse the models to determine how critical the axial force ratio of the shear walls is in terms of collapse probability. The method proposed in the Federal Emergency Management Agency (FEMA) document FEMA P695 was followed to determine the collapse levels for the high-rise structures. A nonlinear analysis was performed to analyse the failure safety of the models. Results indicate that an increase or decrease in the axial force ratios by more than 15% renders the structure either overdesigned or deficient.Â Doi: 10.28991/CEJ-2022-08-03-011 Full Text: PDF